Pengetahuan Keuangan, Sikap Keuangan dan Perilaku Keuangan Kelompok Wirausaha Hasil Laut di Pulau Barrang Lompo - sijal, mutakallim; Awaluddin, Murtiadi; Alifurahman, Alifurahman; Mutmainna, Dian (Study of Scientific and Behavioral Management, 2023)
The purpose of this study was to determine the implications of financial behavior and financial knowledge on the financial attitude of the marine product entrepreneur group on Barrang Lompo Island. This research uses a type of quantitative research using a direct survey process of the community by distributing a number of statements. In this study, the data collection method used was simple random sampling. Based on the results of the f test, it states that the calculated F-value is 33.211 > the F-table value of 3.098 and also has a significant value of 0.000 <0.05, so it can be concluded that financial knowledge and financial attitude variables influence simultaneously or together to financial behavior variables. This means that the higher the financial knowledge and financial attitudes one has, the more effective and wise a person will be in the process of implementing financial aspects, one of which is basic knowledge of finance including saving decisions, income, spending arrangements, debt and other risks. And vice versa, a person will have bad or ineffective financial behavior if he has a lower level of financial knowledge. Someone with a good financial attitude will tend to be wiser in the process of making decisions about their financial behavior. Conversely, someone who has bad financial behavior means that the individual has a bad financial attitude too. Keywords: Financial Behavior, Financial Knowledge and Financial Attitude